Análise das influências do ensino explícito de argumentação nos conhecimentos docentes sobre argumentação de professores de química em formação inicial - Stefannie de Sa Ibraim (2015)
Many authors emphasise the contributions of argumentation to science teaching, the relationship between teachers practice and students argumentation, and the importance of teaches role in generating and conducting argumentative situations in regular classrooms. Therefore, it is essential that teachers have knowledge on argumentation in order to relly so you can effectively promote the occurrence and lead argumentative situations in their science classrooms. This necessity implies that the teacher has, at some point in their training, opportunities to start developing this knowledge, These considerations encourage us to investigate the influences of explicit teaching argumentation in teaching knowledge of chemistry teachers of argument in initial training. In this work, we established two categories of knowledge which we consider essential to the education based on arguments: knowledge of argumentation, which includes elements such as evidence and justification, and the capacity to propose alternative, counter-argument and refute; knowledge and pair the teaching action in argument, which involves the knowledge of teaching strategies and instructional materials, and skills to lead argumentative situations. Therefore, our research was directed to house one of the dimensions of such knowledge. In order to achieve our goal, we follow lessons of a subject of a Bachelor's Degree in Chemistry from a public university for a semester. This course is explicit teaching of argument. All lessons were recorded on video and the materials produced and used by the six students were collected. In addition, field notes were made. The integration of data from different sources has allowed us to build a case study that shows the explicit teaching d argument experienced in the classroom. Data analysis indicated that the explicit teaching of argument influenced the conceptual learning of the students on argumentation, especially in relation to evidence and justifications elements. However, they had some difficulties when they needed to mobilize this knowledge in dialogical situations. Thus, although the students have developed their conceptual knowledge on argumentation, the use of argumentative approach in teaching situations still looks challenging. In addition, we realized that there was an influence on knowledge for teaching activities. However, this seems to have been restricted to the knowledge of teaching strategies and instructional materials. We believe that the mastery of skills to lead argumentative situations has been compromised by other knowledge beyond the scope of explicit teaching of argument. The conclusions of this study point to contributions of argumentation to future teachers knowledge in argumentation-based teaching, to the organisation and structure of teachers initial education in training contexts related to argumentation.